Additional Value Peternak Sapi melalui Olah Limbah Kotoran Sapi Menjadi Biogas Skala Rumah Tangga di Desa Sekarmojo Kecamatan Purwosari Kabupaten Pasuruan - Fauziyah; Achmad Bahul; Marhamah; Yun Suryotomo; Indranata (LPPM Universitas Yudharta Pasuruan, 2021)
Processing cow dung into biogas is one solution that can be offered to cattle breeders in Sekarmojo Pasuruan. This service uses a follow-up approach to the problem of utilizing cow dung waste in Sekarmojo Village as raw material for biogas production. The results of this assistance show additional value results for cattle breeders in Sekarmojo Village Pasuruan including (1) reduced air pollution from cow dung, (2) sharing biogas with neighbors, (3) having the potential for organic fertilizer from biogas slurry, (4) reducing the purchase burden. LPG gas for cooking, as well as (5) cleaner and healthier cowsheds